Serum Metabolomic Patterns in Patients With Aldosterone-Producing Adenoma - Chen, Yule; Wang, Hanjiang; Wang, Ke; Zhu, Guodong; Yang, Zhishang; Wang, Min; Song, Wenbin (Frontiers in Molecular Biosciences, 2022)
Aldosterone-producing adenoma (APA), the main cause of endocrine hypertension, has recently been reported to be associated with other diseases, such as metabolic syndrome, but the detailed mechanism underlying this association remains unclear. Here, we used untargeted metabolomics and compared the abundance of serum metabolites between essential hypertension (EHT) and APA patients, as well as the serum metabolites of APA patients before and after adrenalectomy. Our results revealed 44 differential metabolites between APA and EHT patients and 39 differential metabolites between pre- and postoperative APA patients. Several metabolites involved in cardiovascular disease, obesity, and diabetes were dysregulated in APA patients compared to EHT patients, including <ext-link ext-link-type="uri" xlink:href="http://www.baidu.com/link?url=wT4TRTlnu3AExmCEElo5KAgse5Z_U3F3su86n0o01uNdD0iX-GgRWnScBaEaJRO-1NznRL3dFw6zNwpQaLpHYPAvArEfT8TIsh-d4_4qqEMUYitbTGjVWMmuFC8ZQbvM" xmlns:xlink="http://www.w3.org/1999/xlink">arachidonic acid metabolites [e.g., 5(S)-HpETE and 12-HETE], amino acids (e.g., L-carnitine, taurine, and L-arginine), nucleotide metabolites (e.g., hypoxanthine) and cholesterol 3-sulfate. Importantly, the levels of hypoxanthine and cholesterol 3-sulfate, two metabolites that promote the development of atherosclerotic lesions and obesity, were originally increased in APA patients, but those elevated levels were reversed by adrenalectomy. Conversely, levels of L-carnitine and (3-carboxypropyl) trimethylammonium cation, two metabolites participating in lipid metabolism, were decreased in APA patients but increased postoperatively. We conclude that APA might participate in cardiovascular and metabolic diseases by regulating serum metabolites.